National Courts and Preliminary References to the Court of Justice - Krommendijk, Jasper (Edward Elgar Publishing, 2021)
This innovative book examines why national courts refer preliminary references to the European Court of Justice (ECJ), and what the referring court does with the answers. Jasper Krommendijk highlights the three core stages in the interaction between national courts and the ECJ: question, answer and follow-up, shedding new light on this under-explored area.